2000
DOI: 10.1103/physreve.61.5981
|View full text |Cite
|
Sign up to set email alerts
|

Model for correlations in stock markets

Abstract: We propose a group model for correlations in stock markets. In the group model the markets are composed of several groups, within which the stock price fluctuations are correlated. The spectral properties of empirical correlation matrices reported recently are well understood from the model. It provides the connection between the spectral properties of the empirical correlation matrix and the structure of correlations in stock markets.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
88
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 10 publications
(26 reference statements)
3
88
0
Order By: Relevance
“…Matrix elements of the off-diagonal blocks are 0. Such examples qualitatively correspond to the 'factor model' in quantitative finance [35,36,48], where the off-diagonal blocks have small entries. In a second example, ξ has smooth band structure, e.g., ξ jk = c |j−k| .…”
Section: Emerging Spectra Of Cwoementioning
confidence: 90%
“…Matrix elements of the off-diagonal blocks are 0. Such examples qualitatively correspond to the 'factor model' in quantitative finance [35,36,48], where the off-diagonal blocks have small entries. In a second example, ξ has smooth band structure, e.g., ξ jk = c |j−k| .…”
Section: Emerging Spectra Of Cwoementioning
confidence: 90%
“…This 'noise' could be reduced through the use of longer simulated time series or through averaging over a large number of time series. In order to compare the eigenvectors from each of the Model Correlation matrices and that constructed from the equity returns time series, we use the Inverse Participation Ratio (IPR) [4,22]. The IPR allows quantification of the number of components that participate significantly in each eigenvector and tells us more about the level and nature of deviation from RMT.…”
Section: Market Plus Sectors Modelmentioning
confidence: 99%
“…Here, we show how a simple one-factor model, Section 2.2, of the correlation structure reproduces much of this behaviour. Furthermore, we show how additional features can be captured by including perturbations in this model, essentially a "market plus sectors" model, Section 2.3, [13,22,23].…”
Section: Model Correlation Matrixmentioning
confidence: 99%
“…In a comprehensive study of the U.S. stock market, Plerou et al (2000) found that the deviating non-random eigenvalues were stable in time and that the largest eigenvalue corresponded to a common inuence on all stocks (in line with the market portfolio of the Capital Asset Pricing Model ). Various studies have proposed methods for identication of the non-random elements of the correlation matrix (Laloux et al, 1999;Noh, 2000;Gallucio et al, 1998). It can easily be imagined that ecient frontiers from the original correlation matrix might dier strongly from those generated from a correlation matrix that has been cleaned by eliminating the eigenvalues within the noise band.…”
Section: Analysis Of Correlation Matricesmentioning
confidence: 99%